Pengaruh Persepsi Konsumen terhadap Keputusan Pembelian Ulang pada Indomaret Kecamatan Sungai Bahar - Wiyan Mailindra; Muhammad Amali (Ekonomis: Journal of Economics and Business, 2018)
Retail business in Indonesia can be difided into 2 major groups, namely Tradisional Retail and Modern Retail. Modern retail is developed from tradisional retail. This retail format emerged and developed along with economic development, technology, and society life style which make the society demand more pleasure in doing shopping. Along with retail business development, nowadays retail business has not longer managed tradisionally, but in modern ways, therefore it becomes inovative, dynamic, and compatitive business. This research used primer and secunder data, in which primer data were obtained through interview and  distributing questionare to 80 respondents, meanwhile secunder data where gotten from literature or document related to this research and were grouped into 2 variables, namely dependent variable and independent variabel, in which repurchase decision as dependent variable and consumen perception as independent variable.       The result of this research is consumen perception towards repurchase decision showed by the value thitung is 7,563. With significant value is 0,000 < α = 0,05. Therefore it can be said that there is significant effect of consumen perception toward repurchase decision at indomaret. Then it is seen from the value of thitung above and compared to value of ttabel. To get the value of ttabel, two ways test was done dk = n – 2  and dk = 80 – 2 = 78, if deviation degree is determined 0,05 (5%), so ttabel = 1,665. Because the value of thitung> ttabel it means that Ha is accepted and Ho is rejected. It means that there is significant effect of consumen perception toward repurchase decision at indomaret.